Catalyst for preparing formaldehyde through methanol oxidation as well as preparation method and application of catalyst

By adjusting the pH of molybdenum salt and iron salt and adding vanadium salt, manganese salt and multi-wall carbon nanotubes, a methanol oxidation catalyst is prepared with high stability and good activity, which solves the short service life of existing iron-molybdenum catalysts and The problem of prone to inactivation of active components has achieved efficient catalytic effects.

CN119215924APending Publication Date: 2024-12-31CHANGZHOU XINRI CATALYST CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411347691.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-08
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing iron-molybdenum catalyst has a short service life and the active component Mo is easily sublimated and lost, resulting in the problem of catalyst deactivation.

Method used

By adjusting the pH value of the molybdenum salt solution to acidity, mixing the molybdenum salt with iron salt and mixed with the vanadium salt and manganese salt solution, adding multi-walled carbon nanotubes, and preparing methanol oxidation to make formaldehyde catalyst through crystallization and calcination, using multi-walled As a support, carbon nanotubes evenly distribute Mo, Fe, V, and Mn active components, increase the contact area between the catalyst and methanol, reduce the reaction temperature and improve catalytic activity.

Benefits of technology

It improves the stability and activity of the catalyst, extends the service life, reduces the reaction temperature, and enhances the catalytic activity, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005063149610000091
    Figure BDA0005063149610000091
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of novel catalytic materials, and discloses a catalyst for preparing formaldehyde through methanol oxidation as well as a preparation method and application of the catalyst. The preparation method comprises the following steps: adjusting the pH value of a molybdenum salt solution to be acidic, mixing the molybdenum salt solution with a ferric salt solution, aging, and mixing the obtained product with a vanadium salt solution and a manganese salt solution to obtain first slurry; mixing a multi-walled carbon nanotube with ethanol to obtain a second slurry; and mixing the first slurry and the second slurry, crystallizing and calcining to obtain the methanol oxidation formaldehyde catalyst. According to the catalyst for preparing formaldehyde through methanol oxidation, the multi-walled carbon nanotube serves as a carrier, Mo, Fe, V and Mn serve as active components, the catalyst has excellent reaction activity, the active components are not prone to inactivation, the preparation method is easy to operate, and the catalyst can be applied to the industrial production field of preparing formaldehyde through methanol oxidation.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application. The application number of the parent application is 202311695448.5. The application date is December 8, 2023. The name of the invention is "A catalyst for producing formaldehyde by methanol oxidation, its preparation method and application". Technical Field

[0002] The invention relates to the technical field of novel catalytic material preparation, and in particular to a catalyst for preparing formaldehyde by oxidation of methanol, and a preparation method and application thereof. Background Art

[0003] As an important basic chemical raw material, formaldehyde is widely used in the production of various resins, adhesives, hexamine, pyridine and its derivatives and other chemical products. Its market demand has maintained a growth trend in recent years. Formaldehyde can be produced from methanol, dimethyl ether, natural gas and other raw materials. Among them, the methanol-to-formaldehyde process is the most widely used. According to the type of catalyst, it can be divided into the silver method and the iron-molybdenum method. Compared with the silver method, the iron-molybdenum method has the advantages of low reaction temperature, high methanol conversion rate, high formaldehyde product concentration and good economic benefits.

[0004] However, the existing iron-molybdenum catalyst has the disadvantages of short service life and easy sublimation loss of the active component Mo. Patent CN108435192A discloses a mechanochemical synthesis method of an iron-molybdenum catalyst for methanol oxidation to formaldehyde, which is prepared by mixing molybdate and iron salt through ball milling and calcination, and has the advantages of good selectivity and activity. However, it still has the problem of easy deactivation of the catalyst.

[0005] Therefore, providing an iron-molybdenum catalyst with long service life and good activity is a technical problem that urgently needs to be solved. Summary of the invention

[0006] The purpose of the present invention is to provide a catalyst for preparing formaldehyde by oxidation of methanol and a preparation method and application thereof, so as to solve the problems in the prior art.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a catalyst for producing formaldehyde by oxidation of methanol, comprising the following steps:

[0009] Adjusting the pH value of the molybdenum salt solution to acidic, mixing the molybdenum salt solution with the iron salt solution, aging, and mixing the obtained product with the vanadium salt solution and the manganese salt solution to obtain a first slurry;

[0010] mixing the multi-walled carbon nanotubes with ethanol to obtain a second slurry;

[0011] The first slurry and the second slurry are mixed, and the catalyst for producing formaldehyde by oxidation of methanol is obtained through crystallization and calcination.

[0012] Preferably, in the above-mentioned method for preparing a catalyst for producing formaldehyde by oxidation of methanol, the molar ratio of the molybdenum element in the molybdenum salt solution to the iron element in the iron salt solution is 1.6 to 5.5:1;

[0013] The molar ratio of the vanadium element in the vanadium salt solution to the iron element in the iron salt solution is 0.1 to 2:1;

[0014] The molar ratio of manganese in the manganese salt solution to iron in the iron salt solution is 0.3 to 1.5:1;

[0015] The mass volume ratio of molybdenum element to multi-walled carbon nanotubes and ethanol in the molybdenum salt solution is 1g:0.5-1.5g:20-30mL.

[0016] Preferably, in the above-mentioned method for preparing a catalyst for producing formaldehyde by oxidation of methanol, the concentration of the molybdenum salt solution is 0.01 to 10 g / mL;

[0017] The concentration of the iron salt solution is 0.01 to 10 g / mL;

[0018] The concentration of the vanadium salt solution is 0.01 to 10 g / mL;

[0019] The concentration of the manganese salt solution is 0.01-5 g / mL.

[0020] Preferably, in the above-mentioned method for preparing a catalyst for producing formaldehyde by oxidation of methanol, the molybdenum salt in the molybdenum salt solution is one or more of ammonium molybdate, sodium molybdate, lithium molybdate, and potassium molybdate;

[0021] The iron salt in the iron salt solution is one or more of ferric nitrate, ferric oxalate, ferric sulfate and ferric chloride;

[0022] The vanadium salt in the vanadium salt solution is one or more of vanadyl sulfate, vanadyl oxalate, and vanadyl dichloride;

[0023] The manganese salt in the manganese salt solution is one or more of manganese sulfate, manganese chloride and manganese nitrate.

[0024] Preferably, in the above-mentioned method for preparing a catalyst for producing formaldehyde by oxidation of methanol, the temperature at which the molybdenum salt solution and the iron salt solution are mixed is 40 to 80°C.

[0025] Preferably, in the above-mentioned method for preparing a catalyst for producing formaldehyde by oxidation of methanol, the aging temperature is 25 to 150° C., and the aging time is 5 to 24 hours.

[0026] Preferably, in the above-mentioned method for preparing a catalyst for producing formaldehyde by oxidation of methanol, the crystallization temperature is 100 to 230° C., and the crystallization time is 6 to 24 hours.

[0027] Preferably, in the above-mentioned method for preparing a catalyst for producing formaldehyde by oxidation of methanol, the calcination temperature is 300 to 400° C., and the calcination time is 5 to 48 hours.

[0028] The invention also provides a catalyst for preparing formaldehyde through oxidation of methanol, which is prepared by a method for preparing the catalyst for preparing formaldehyde through oxidation of methanol.

[0029] The present invention also provides an application of a catalyst for preparing formaldehyde through oxidation of methanol in preparing formaldehyde through oxidation of methanol.

[0030] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0031] (1) The methanol oxidation to formaldehyde catalyst of the present invention uses multi-walled carbon nanotubes as carriers and Mo, Fe, V, and Mn as active components. The multi-walled carbon nanotubes have a hollow tubular structure with a large specific surface area. The Mo, Fe, V, and Mn active components can be evenly distributed on the multi-walled carbon nanotubes, which can increase the effective contact area between the catalyst and methanol, thereby improving the stability of the catalyst. On the basis of the Mo and Fe active components, the addition of V and Mn can reduce the reaction temperature and improve the catalytic activity.

[0032] (2) The preparation method of the present invention is simple to operate, the prepared catalyst has excellent reaction activity, and the active components are not easily deactivated, and can be applied to the industrial production field of methanol oxidation to formaldehyde. DETAILED DESCRIPTION

[0033] The present invention provides a method for preparing a catalyst for producing formaldehyde by oxidation of methanol, comprising the following steps:

[0034] Adjusting the pH value of the molybdenum salt solution to acidic, mixing the molybdenum salt solution with the iron salt solution, aging, and mixing the obtained product with the vanadium salt solution and the manganese salt solution to obtain a first slurry;

[0035] mixing the multi-walled carbon nanotubes with ethanol to obtain a second slurry;

[0036] The first slurry and the second slurry are mixed, and the catalyst for producing formaldehyde by oxidation of methanol is obtained through crystallization and calcination.

[0037] In the present invention, the specific method for adjusting the pH value of the molybdenum salt solution to acidic is:

[0038] The pH value of the molybdenum salt solution is adjusted to 1-4 by using a nitric acid solution, and the concentration of the nitric acid solution is preferably 65-72wt%, more preferably 66-70wt%, and more preferably 67-69wt%.

[0039] In the present invention, the molybdenum salt solution and the iron salt solution are preferably mixed in the following manner:

[0040] The iron salt solution is heated to a mixing temperature, and the iron salt solution is added dropwise to the molybdenum salt solution under stirring. There is no particular limitation on the stirring speed and the dropping speed in the present invention.

[0041] In the present invention, the temperature at which the molybdenum salt solution and the iron salt solution are mixed is preferably 40 to 80°C, more preferably 45 to 70°C, and even more preferably 50 to 62°C.

[0042] In the present invention, the aging temperature is preferably 25 to 150° C., more preferably 38 to 125° C., and more preferably 50 to 110° C.; the aging time is preferably 5 to 24 h, more preferably 7 to 20 h, and more preferably 10 to 17 h.

[0043] In the present invention, the molar ratio of the molybdenum element in the molybdenum salt solution to the iron element in the iron salt solution is preferably 1.6 to 5.5:1, more preferably 2.2 to 5:1, and more preferably 3.3 to 4.1:1;

[0044] The molar ratio of the vanadium element in the vanadium salt solution to the iron element in the iron salt solution is preferably 0.1 to 2:1, more preferably 0.3 to 1.7:1, and more preferably 0.9 to 1.4:1;

[0045] The molar ratio of manganese in the manganese salt solution to iron in the iron salt solution is preferably 0.3 to 1.5:1, more preferably 0.5 to 1.2:1, and more preferably 0.7 to 1:1;

[0046] The mass volume ratio of molybdenum element to multi-walled carbon nanotubes and ethanol in the molybdenum salt solution is preferably 1g:0.5-1.5g:20-30mL, further preferably 1g:0.7-1.2g:22-28mL, and more preferably 1g:0.9-1g:25-27mL.

[0047] In the present invention, the concentration of the molybdenum salt solution is preferably 0.01 to 10 g / mL, more preferably 0.05 to 7 g / mL, and more preferably 2 to 5 g / mL;

[0048] The concentration of the iron salt solution is preferably 0.01 to 10 g / mL, more preferably 0.5 to 8 g / mL, and more preferably 4 to 6 g / mL;

[0049] The concentration of the vanadium salt solution is preferably 0.01 to 10 g / mL, more preferably 0.5 to 8 g / mL, and more preferably 4 to 6 g / mL;

[0050] The concentration of the manganese salt solution is preferably 0.01 to 5 g / mL, more preferably 0.8 to 4 g / mL, and even more preferably 2 to 3 g / mL.

[0051] In the present invention, the molybdenum salt in the molybdenum salt solution is preferably one or more of ammonium molybdate, sodium molybdate, lithium molybdate, and potassium molybdate, further preferably one or more of ammonium molybdate, sodium molybdate, and lithium molybdate, more preferably one or two of ammonium molybdate and sodium molybdate;

[0052] The iron salt in the iron salt solution is preferably one or more of ferric nitrate, ferric oxalate, ferric sulfate, and ferric chloride, more preferably one or more of ferric nitrate, ferric oxalate, and ferric sulfate, and more preferably one or two of ferric nitrate and ferric oxalate;

[0053] The vanadium salt in the vanadium salt solution is preferably one or more of vanadyl sulfate, vanadyl oxalate, and vanadyl dichloride, more preferably one or two of vanadyl sulfate and vanadyl oxalate, and more preferably vanadyl sulfate;

[0054] The manganese salt in the manganese salt solution is preferably one or more of manganese sulfate, manganese chloride and manganese nitrate, more preferably one or two of manganese sulfate and manganese chloride, and more preferably manganese sulfate.

[0055] In the present invention, the crystallization temperature is preferably 100-230°C, more preferably 120-200°C, and more preferably 150-180°C; the crystallization time is preferably 6-24h, more preferably 10-20h, and more preferably 13-17h.

[0056] In the present invention, after the crystallization is completed, the method further comprises:

[0057] The slurry obtained by crystallization is washed with deionized water, and then filtered to obtain a filter cake, which is then washed with deionized water.

[0058] In the present invention, the calcination temperature is preferably 300-400°C, more preferably 312-375°C, and more preferably 345-355°C; the calcination time is preferably 5-48h, more preferably 10-40h, and more preferably 12-24h.

[0059] The invention also provides a catalyst for preparing formaldehyde through oxidation of methanol, which is prepared by a method for preparing the catalyst for preparing formaldehyde through oxidation of methanol.

[0060] The present invention also provides an application of a catalyst for preparing formaldehyde through oxidation of methanol in preparing formaldehyde through oxidation of methanol.

[0061] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0062] Example 1

[0063] Dissolve 29.4 g of ammonium molybdate in 200 mL of water to obtain a molybdenum salt solution, dissolve 12.1 g of ferric nitrate in 120 mL of water to obtain an iron salt solution, dissolve 4.075 g of vanadium sulfate in 50 mL of water to obtain a vanadium salt solution, and dissolve 7.55 g of manganese sulfate in 70 mL of water to obtain a manganese salt solution;

[0064] A 65 wt % nitric acid solution is added to the molybdenum salt solution to adjust the pH of the molybdenum salt solution to 2; the iron salt solution is heated to 50° C., and then the heated iron salt solution is added dropwise to the acidified molybdenum salt solution under stirring at a speed of 500 r / min, and then aged at 100° C. for 12 hours; after the aging is completed, the obtained product is mixed with a vanadium salt solution and a manganese salt solution to obtain a first slurry;

[0065] Mixing 20 g of multi-walled carbon nanotubes with 350 mL of ethanol to obtain a second slurry;

[0066] The first slurry and the second slurry are mixed, crystallized at 150°C for 12 hours to obtain a slurry, the slurry is washed with deionized water, and then filtered to obtain a filter cake, which is further washed with deionized water. The washed filter cake is calcined at 350°C for 24 hours to obtain a methanol oxidation to formaldehyde catalyst.

[0067] Example 2

[0068] 62.64 g of lithium molybdate was dissolved in 500 mL of water to obtain a molybdenum salt solution, 32 g of ferric sulfate was dissolved in 200 mL of water to obtain an iron salt solution, 15.68 g of vanadium oxalate was dissolved in 200 mL of water to obtain a vanadium salt solution, and 12 g of manganese chloride was dissolved in 150 mL of water to obtain a manganese salt solution;

[0069] A 68 wt % nitric acid solution is added to the molybdenum salt solution to adjust the pH value of the molybdenum salt solution to 2.5; the iron salt solution is heated to 65° C., and then the heated iron salt solution is added dropwise to the acidified molybdenum salt solution under stirring at a speed of 650 r / min, and then aged at 150° C. for 10 hours; after the aging is completed, the obtained product is mixed with a vanadium salt solution and a manganese salt solution to obtain a first slurry;

[0070] Mixing 35 g of multi-walled carbon nanotubes with 700 mL of ethanol to obtain a second slurry;

[0071] The first slurry and the second slurry are mixed, crystallized at 200°C for 8 hours to obtain a slurry, the slurry is washed with deionized water, and then filtered to obtain a filter cake, which is further washed with deionized water. The washed filter cake is calcined at 400°C for 10 hours to obtain a methanol oxidation to formaldehyde catalyst.

[0072] Example 3

[0073] Dissolve 55 g of ammonium molybdate in 400 mL of water to obtain a molybdenum salt solution, dissolve 17 g of ferric nitrate in 100 mL of water to obtain an iron salt solution, dissolve 17 g of vanadium sulfate in 100 mL of water to obtain a vanadium salt solution, and dissolve 10.5 g of manganese sulfate in 100 mL of water to obtain a manganese salt solution;

[0074] A 70 wt % nitric acid solution is added to the molybdenum salt solution to adjust the pH value of the molybdenum salt solution to 1.5; the iron salt solution is heated to 70° C., and then the heated iron salt solution is added dropwise to the acidified molybdenum salt solution under stirring at a speed of 600 r / min, and then aged at 75° C. for 15 hours; after the aging, the obtained product is mixed with a vanadium salt solution and a manganese salt solution to obtain a first slurry;

[0075] Mixing 30 g of multi-walled carbon nanotubes with 550 mL of ethanol to obtain a second slurry;

[0076] The first slurry and the second slurry are mixed, crystallized at 200°C for 15 hours to obtain a slurry, the slurry is washed with deionized water, and then filtered to obtain a filter cake, which is further washed with deionized water. The washed filter cake is calcined at 380°C for 20 hours to obtain a methanol oxidation to formaldehyde catalyst.

[0077] Example 4

[0078] Dissolve 59.5 g of potassium molybdate in 500 mL of water to obtain a molybdenum salt solution, dissolve 20 g of ferric sulfate in 150 mL of water to obtain an iron salt solution, dissolve 15 g of vanadium sulfate in 50 mL of water to obtain a vanadium salt solution, and dissolve 6.3 g of manganese nitrate in 50 mL of water to obtain a manganese salt solution;

[0079] A 65 wt % nitric acid solution is added to the molybdenum salt solution to adjust the pH of the molybdenum salt solution to 2; the iron salt solution is heated to 50° C., and then the heated iron salt solution is added dropwise to the acidified molybdenum salt solution under stirring at a speed of 500 r / min, and then aged at 100° C. for 12 hours; after the aging is completed, the obtained product is mixed with a vanadium salt solution and a manganese salt solution to obtain a first slurry;

[0080] Mixing 20 g of multi-walled carbon nanotubes with 350 mL of ethanol to obtain a second slurry;

[0081] The first slurry and the second slurry are mixed, crystallized at 150°C for 12 hours to obtain a slurry, the slurry is washed with deionized water, and then filtered to obtain a filter cake, which is further washed with deionized water. The washed filter cake is calcined at 350°C for 24 hours to obtain a methanol oxidation to formaldehyde catalyst.

[0082] Example 5

[0083] Dissolve 39.2 g of ammonium molybdate in 200 mL of water to obtain a molybdenum salt solution, dissolve 24.2 g of ferric nitrate in 120 mL of water to obtain an iron salt solution, dissolve 8 g of vanadium sulfate in 50 mL of water to obtain a vanadium salt solution, and dissolve 12 g of manganese sulfate in 50 mL of water to obtain a manganese salt solution;

[0084] A 65 wt % nitric acid solution is added to the molybdenum salt solution to adjust the pH of the molybdenum salt solution to 2; the iron salt solution is heated to 50° C., and then the heated iron salt solution is added dropwise to the acidified molybdenum salt solution under stirring at a speed of 500 r / min, and then aged at 115° C. for 10 hours; after the aging is completed, the obtained product is mixed with a vanadium salt solution and a manganese salt solution to obtain a first slurry;

[0085] Mixing 20 g of multi-walled carbon nanotubes with 350 mL of ethanol to obtain a second slurry;

[0086] The first slurry and the second slurry are mixed, crystallized at 180°C for 15 hours to obtain a slurry, the slurry is washed with deionized water, and then filtered to obtain a filter cake, which is further washed with deionized water. The washed filter cake is calcined at 320°C for 26 hours to obtain a methanol oxidation to formaldehyde catalyst.

[0087] Comparative Example 1

[0088] Dissolve 29.4 g of ammonium molybdate in 200 mL of water to obtain a molybdenum salt solution, dissolve 12.1 g of ferric nitrate in 120 mL of water to obtain an iron salt solution, dissolve 4.075 g of vanadium sulfate in 50 mL of water to obtain a vanadium salt solution, and dissolve 7.55 g of manganese sulfate in 70 mL of water to obtain a manganese salt solution;

[0089] A 65 wt % nitric acid solution is added to the molybdenum salt solution to adjust the pH value of the molybdenum salt solution to 2; the iron salt solution is heated to 50° C., and then the heated iron salt solution is added dropwise to the acidified molybdenum salt solution under stirring at a speed of 500 r / min, and then aged at 100° C. for 12 hours; after the aging, the obtained product is mixed with a vanadium salt solution and a manganese salt solution, and then crystallized at 150° C. for 12 hours to obtain a slurry, the slurry is washed with deionized water, and then filtered to obtain a filter cake, which is further washed with deionized water, and the washed filter cake is calcined at 350° C. for 24 hours to obtain a methanol oxidation to formaldehyde catalyst.

[0090] Comparative Example 2

[0091] Dissolve 29.4 g of ammonium molybdate in 200 mL of water to obtain a molybdenum salt solution, and dissolve 12.1 g of ferric nitrate in 120 mL of water to obtain an iron salt solution;

[0092] Adding 65 wt % nitric acid solution to the molybdenum salt solution to adjust the pH of the molybdenum salt solution to 2; heating the iron salt solution to 50° C., then dropping the heated iron salt solution into the acidified molybdenum salt solution under stirring at a speed of 500 r / min, and then aging at 100° C. for 12 hours; after the aging, obtaining a first slurry;

[0093] Mixing 20 g of multi-walled carbon nanotubes with 350 mL of ethanol to obtain a second slurry;

[0094] The first slurry and the second slurry are mixed, crystallized at 150°C for 12 hours to obtain a slurry, the slurry is washed with deionized water, and then filtered to obtain a filter cake, which is further washed with deionized water. The washed filter cake is calcined at 350°C for 24 hours to obtain a methanol oxidation to formaldehyde catalyst.

[0095] The performance of the methanol oxidation catalyst prepared in the embodiment and the comparative example was tested. The reaction conditions were: reaction temperature of 260°C, volume content of imported methanol of 6.8%, and space velocity of 12000h -1 The test results are shown in Table 1.

[0096] Table 1 Performance test results of methanol oxidation to formaldehyde catalyst

[0097]

[0098] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a catalyst for producing formaldehyde by oxidation of methanol, characterized in that: The following steps are involved: Adjusting the pH value of the lithium molybdate solution to acidic, mixing the lithium molybdate solution with a ferric sulfate solution, and aging the mixture, and mixing the obtained product with a vanadyl oxalate solution and a manganese chloride solution to obtain a first slurry; mixing the multi-walled carbon nanotubes with ethanol to obtain a second slurry; The first slurry and the second slurry are mixed, and the mixture is crystallized and calcined to obtain a catalyst for producing formaldehyde by oxidation of methanol; The temperature at which the lithium molybdate solution and the ferric sulfate solution are mixed is 65° C. The aging temperature is 150°C and the aging time is 10h; The crystallization temperature is 200° C. and the crystallization time is 8 h; The mass ratio of lithium molybdate in the lithium molybdate solution to ferric sulfate in the ferric sulfate solution is 62.64:32; The mass volume ratio of lithium molybdate to multi-walled carbon nanotubes and ethanol in the lithium molybdate solution is 62.64 g:35 g:700 mL.

2. The method for preparing a catalyst for producing formaldehyde by oxidation of methanol according to claim 1, characterized in that: The mass ratio of vanadyl oxalate in the vanadyl oxalate solution to ferric sulfate in the ferric sulfate solution is 15.68:32; The mass ratio of manganese chloride in the manganese chloride solution to ferric sulfate in the ferric sulfate solution is 12:

32.

3. The method for preparing a catalyst for producing formaldehyde by oxidation of methanol according to claim 1 or 2, characterized in that: The concentration of the lithium molybdate solution is 125.28 g / L; The concentration of the ferric sulfate solution is 160 g / L; The concentration of the vanadyl oxalate solution is 78.4 g / L; The concentration of the manganese chloride solution is 80 g / L.

4. The method for preparing a catalyst for producing formaldehyde by oxidation of methanol according to claim 1, characterized in that: The calcination temperature is 400° C., and the calcination time is 10 h.

5. The catalyst for preparing formaldehyde through methanol oxidation obtained by the method for preparing the catalyst for preparing formaldehyde through methanol oxidation according to any one of claims 1 to 4.

6. Use of the catalyst for preparing formaldehyde by oxidation of methanol as claimed in claim 5 in preparing formaldehyde by oxidation of methanol.

Citation Information

Patent Citations

  • Mechanochemical synthesis method of iron-molybdenum catalyst for preparing formaldehyde with methanol oxidation

    CN108435192A